1993
DOI: 10.1038/361365a0
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 blocks apoptosis in cells lacking mitochondrial DNA

Abstract: When the mammalian proto-oncogene bcl-2 is overexpressed it can protect various types of cells both from normal and from experimentally induced apoptosis, but the molecular mechanisms involved are unknown. Although the Bcl-2 protein is membrane-associated, its subcellular location is controversial: two studies have suggested that it is mainly associated with the nuclear envelope and endoplasmic reticulum, whereas another study has suggested that it is mainly located in the inner mitochondrial membrane. The lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
322
3
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 699 publications
(364 citation statements)
references
References 29 publications
32
322
3
7
Order By: Relevance
“…15 Early evidence showed that cultured cells lacking mitochondrial DNA and therefore deficient in respiration could undergo apoptosis, suggesting that MRC is not necessary for apoptosis. 35,36 Recent evidence, however, also indicates that the physiological functions of mitochondria are involved in cell death. 15 As examples, reports show that a functional electron transport chain regulates oxygen deprivation-induced cell death, and an ATP synthase is required in TNF-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Early evidence showed that cultured cells lacking mitochondrial DNA and therefore deficient in respiration could undergo apoptosis, suggesting that MRC is not necessary for apoptosis. 35,36 Recent evidence, however, also indicates that the physiological functions of mitochondria are involved in cell death. 15 As examples, reports show that a functional electron transport chain regulates oxygen deprivation-induced cell death, and an ATP synthase is required in TNF-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, since caspases possessing substrate speci®city similar to that of caspase-3 likely function most downstream in the caspase cascade, we conclude that there are no functional sites of Bcl-2 and Bcl-x L downstream of the caspase cascade. Although several groups have shown that Bcl-2 protein localizes in multiple membrane compartments (Hockenbery et al, 1990;Monaghan et al, 1992;Jacobson et al, 1993;Krajewski et al, 1993;Akao et al, 1994), it has not been convincingly determined in which subcellular compartment Bcl-2 acts to prevent cell death. Since active caspase-3 induces apoptotic changes of nuclei in vivo when microinjected into the cytoplasm (Yasuhara et al, 1997, and this study) and also in vitro when incubated with naked nuclei and cell lysates (Enari et al, 1996), caspase-3-mediated death signals or the caspase itself must be transferred from the cytoplasm to the nucleus to induce apoptotic nuclear changes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Bcl-2 acts at least upstream of the activation of caspases. Bcl-2 localizes in multiple membrane compartments, including the nuclear envelope, endoplasmic reticulum and mitochondrial membranes (Hockenbery et al, 1990;Monaghan et al, 1992;Jacobson et al, 1993;Krajewski et al, 1993;Akao et al, 1994), raising the possibility that Bcl-2 also acts downstream of caspases. Indeed an anti-cell death role for Bcl-2 exerted downstream of active ICE family proteases has been suggested by the observations that (1) using in vitro apoptosis system, apoptotic DNA ladder formation is prevented by a Bcl-2-containing cell lysate, even after an e ector(s) downstream of caspases is activated, as judged by the failure of caspase inhibitors to prevent apoptotic changes in naked nuclei (Enari et al, 1995) and (2) apoptosis induced by transfection with caspase genes which encode precursor forms of proteases is prevented by overexpressed Bcl-2 (Miura et al, 1993;Wang et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, these solutions do not circumvent a major drawback, which is that ρ 0 cells still contain functional mitochondria. For example, mitochondrial apoptosis proceeds efficiently in ρ 0 cells 20 . This prompted us to develop a method to remove mitochondria, allowing the study of cellular functions in the absence of all aspects of mitochondrial biology.…”
Section: Development Of An Assay That Allows the Generation Of Mitochmentioning
confidence: 99%